An Update: NIH Research Funding for Palliative Medicine, 2011–2015 - Brown, Elizabeth (J Palliat Med, 2018)
Background: The evidence base to support palliative care clinical practice is inadequate and opportunities to improve the palliative care evidence base remain despite the field's rapid growth. Objective: To examine current NIH funding of palliative medicine research, changes since our 2013 report, and trends since our 2008 report. Design: We sought to identify NIH funding of palliative medicine from 2011 to 2015 in two stages: (I) we searched the NIH grants database “RePorter” for grants with key words “palliative care,” “end-of-life care,” “hospice,” and “end of life” and (II) we identified palliative care researchers likely to have secured NIH funding using three strategies. Methods: We abstracted (1) the first and last authors' names from original investigations published in major palliative medicine journals from 2013 to 2015; (2) these names from a PubMed-generated list of original articles published in major medicine, nursing, and subspecialty journals using the above key words; and (3) palliative medicine journal editorial board members and key members of palliative medicine initiatives. We crossmatched the pooled names against NIH grants funded from 2011 to 2015. Results: The author and NIH RePorter search identified 854 and 419 grants, respectively. The 461 grants categorized as relevant to palliative medicine represented 334 unique PIs. Compared to 2006–2010, the number of NIH-funded junior career development awards nearly doubled (6.1%–10%), articles published in nonpalliative care specialty journals tripled (13%–37%), published palliative care researchers increased by 2.5-fold (839–2120), and NIH-funded original palliative medicine research articles doubled (21%–39%). Conclusions: Despite the challenging NIH funding climate, NIH funding to palliative care remained stable. The increase in early stage career development funding, palliative care investigators, and palliative medicine research published in nonpalliative medicine journals reflects important advances to address the workforce and evidence gaps. Further support for palliative care research is still needed.